Iron-based soft magnetic composite material and preparation method thereof

Through particle size grading, refined reduction and phosphoric acid passivation treatment, and using aminopropyltriethoxysilane and tetraethoxysilane to form a multi-layer insulating coating layer, the problems of high-frequency magnetic loss and insulating layer damage of iron powder core soft magnetic composite materials are solved, and iron-based soft magnetic composite materials with low magnetic loss and good insulation performance are achieved.

CN119694701APending Publication Date: 2025-03-25LAIWU IRON & STEEL GRP POWDER METALLURGY CO LTD +1

Patent Information

Application Number
CN202411848893.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing iron powder core soft magnetic composite materials have a large magnetic loss at high frequency, and the insulating coating is prone to deform and rupture during press forming and annealing, resulting in a decrease in magnet resistivity and an increase in eddy current loss.

Method used

Water-atomized iron powder with different particle sizes is used for particle size grading, and the iron powder is refined and reduced. Then the iron powder is passivated by using a phosphoric acid solution to form iron phosphide powder. Then, the insulating treatment is carried out by using aminopropyltriethoxysilane and tetraethoxysilane to form a multi-layer insulating coating layer to reduce damage to the insulating layer during pressing and annealing.

Benefits of technology

It effectively reduces the magnetic loss of iron-based soft magnetic composite materials, maintains good insulation performance, and extends the frequency range of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119694701A_ABST
    Figure CN119694701A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-based soft magnetic composite material and a preparation method thereof, and relates to the technical field of soft magnetic composite materials. According to the method, water atomized iron powder with different particle sizes is adopted for particle size grading, so that pores among iron powder with large particle sizes are filled with iron powder with small particle sizes, after fine reduction treatment is conducted on the iron powder, passivating treatment is conducted on the iron powder subjected to fine reduction treatment through a phosphoric acid solution, and phosphatized iron powder is obtained; the preparation method comprises the following steps: preparing an iron-based soft magnetic composite material, carrying out insulation treatment by using aminopropyltriethoxysilane and tetraethoxysilane to obtain insulated iron powder, adding a lubricant, and carrying out pressing and annealing to obtain the iron-based soft magnetic composite material. When the soft magnetic composite material is prepared, during compression molding, the surface insulation coating layer is less damaged, and after annealing, the soft magnetic composite material is good in insulation performance and low in magnetic loss. In addition, the aminopropyltriethoxysilane and the tetraethoxysilane are adopted for insulation treatment together, and a synergistic effect is achieved on reduction of the magnetic loss of the iron-based soft magnetic material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soft magnetic composite materials, and in particular to an iron-based soft magnetic composite material and a preparation method thereof. Background Art

[0002] Soft magnetic composite materials, also called magnetic powder cores, are generally made by coating a high-resistivity substance on the surface of a metal-based magnetic powder and then pressing it into shape using powder metallurgy. The resulting soft magnetic composite materials have a unique structure of insulation between magnetic particles, which can effectively block the eddy current effect between particles caused by high-frequency operation. It not only solves the problems of low resistivity and high loss of soft magnetic materials, but also retains the good magnetic properties of metal soft magnetic materials.

[0003] Soft magnetic composite materials are classified according to the composition of the magnetic matrix, including pure Fe, FeSi, FeSiCr, etc. Among them, pure iron powder soft magnetic composite materials are generally obtained by molding and heat treatment processes after using reduced iron powder or carbonyl iron powder with a purity of 99.5% as the magnetic matrix after insulation coating. The characteristics of pure iron soft magnetic composite materials are high saturation magnetization and suitable for high-power devices. However, the iron powder core has the problem of large high-frequency loss. Therefore, in order to improve the electromagnetic conversion efficiency of electronic components, reducing the magnetic loss of the iron powder core and expanding the frequency range of use of the iron powder core is an urgent problem to be solved. However, in the process of preparing soft magnetic composite materials, due to the low intrinsic resistivity of pure iron powder, the uniform integrity of its high-resistivity insulating coating layer on the surface is crucial to reducing the magnetic loss of the soft magnetic composite material. The pressing and molding operation will cause the insulating coating to deform and rupture, so that the iron powder on the surface of the magnet is directly exposed, which reduces the resistivity of the magnet and increases the eddy current loss. At the same time, during the annealing process, the insulating coating will be thermally decomposed during the annealing process.

[0004] In the prior art, CN111354528A discloses a phosphoric acid-silane co-coated metal soft magnetic composite material and a preparation method thereof. The phosphoric acid-silane co-coated metal soft magnetic composite material is made of metal soft magnetic powder as raw material. The soft magnetic powder is first phosphated and then transferred to a silane hydrolyzate to form a metal phosphate and silane co-coating layer on the powder surface. Its total loss at 50mT and 100kHz is 90-380W / kg. CN110246675A discloses a high saturation flux density, low loss soft magnetic composite material and a preparation method thereof. Specifically, iron powder is mixed with phosphoric acid to obtain phosphoric acid-coated iron powder, which is then mixed with a coupling agent to obtain an organic insulating layer-coated iron powder. After compression molding and annealing, a soft magnetic composite material is obtained, and its magnetic loss at 30kHz and 0.1T is 107-166W / kg. Although the above-mentioned soft magnetic composite material also uses phosphoric acid to passivate the iron powder and then performs organic insulation treatment, the magnetic loss rate of the obtained soft magnetic composite material is relatively high, which may be caused by deformation and rupture of the insulating coating layer.

[0005] Therefore, it is necessary to prepare an iron-based soft magnetic composite material so that the uniform stability of the surface insulating coating can be ensured after pressing and annealing, thereby reducing the magnetic loss of the iron-based soft magnetic composite material to ensure the insulation performance of the material. Summary of the invention

[0006] In view of the above-mentioned prior art, the purpose of the present invention is to provide an iron-based soft magnetic composite material and a preparation method thereof. The present invention uses water-atomized iron powder of different particle sizes for particle size grading, so that the iron powder of small particle size is filled in the pores between the iron powder of large particle size, and the iron powder is subjected to fine reduction treatment, and the iron powder after fine reduction is passivated by phosphoric acid solution to obtain phosphated iron powder; aminopropyltriethoxysilane and tetraethoxysilane are then used together for insulation treatment to obtain insulating iron powder; lubricant is added and pressed and annealed to obtain an iron-based soft magnetic composite material. The present invention uses the above-mentioned two silane coupling agents to treat the phosphated iron powder, which can react and form a film on the surface of the phosphated iron powder, thereby ensuring that the inorganic oxide is fully combined with the Fe powder to drive the nano inorganic oxide to be deposited on the surface of the iron-based soft magnetic powder. At the same time, it can effectively reduce the damage to the insulating coating layer on the surface of the soft magnetic composite material during the pressing and annealing stages, and the obtained soft magnetic composite material has good insulation performance and low magnetic loss. In addition, the present invention adopts aminopropyltriethoxysilane and tetraethoxysilane to perform insulation treatment together, which has a synergistic effect in reducing the magnetic loss of the iron-based soft magnetic material.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] A first aspect of the present invention provides a method for preparing an iron-based soft magnetic composite material, comprising the following steps:

[0009] (1) performing fine reduction treatment on the iron powder to obtain fine reduced iron powder;

[0010] (2) adding phosphoric acid solution to the refined reduced iron powder and stirring to passivate the refined reduced iron powder to obtain phosphated iron powder;

[0011] (3) adding iron phosphide powder to aminopropyltriethoxysilane solution and stirring to obtain a mixture; adding tetraethoxysilane to the mixture for reaction, and after the reaction is completed, washing and drying to obtain insulating iron powder;

[0012] (4) After adding lubricant to the insulating iron powder, pressing and molding, annealing in a protective gas atmosphere, cooling, washing and drying, the iron-based soft magnetic composite material is obtained.

[0013] Preferably, in step (1), the iron powder is obtained by mixing 80-mesh and 100-mesh water-atomized pure iron powders in a mass ratio of 2:1, and the particle size of the water-atomized iron powder is ≤180 μm.

[0014] Preferably, in step (1), the operation of subjecting the iron powder to fine reduction treatment is: placing the iron powder in a hydrogen atmosphere and treating it at 650-750° C. for 25-35 min to obtain fine reduced iron powder.

[0015] Preferably, in step (1), the purity of the refined reduced iron powder is greater than 99.5%, the particle size is 75-200 μm, and the bulk density is 3.0-3.0 g / cm 3 .

[0016] Preferably, in step (2), the phosphoric acid solution is prepared by mixing phosphoric acid and anhydrous ethanol in a solid-liquid ratio of 1 g: (35-45) mL.

[0017] Preferably, in step (2), the material-liquid ratio of refined reduced iron powder to phosphoric acid solution is (2.5-5) g:1 mL.

[0018] Preferably, in step (2), the stirring temperature is 50-80° C. and the stirring time is 40-60 min.

[0019] Preferably, in step (3), the aminopropyltriethoxysilane solution is prepared by mixing aminopropyltriethoxysilane, anhydrous ethanol and water in a mass ratio of (0.8-1.2):20:10.

[0020] Preferably, in step (3), the material-liquid ratio of the iron phosphide powder and the aminopropyltriethoxysilane solution is (0.8-1.2) g: 2.5 mL.

[0021] Preferably, in step (3), the material-liquid ratio of tetraethoxysilane solution to the mixture is 1 mL: (50-100) g.

[0022] Preferably, in step (3), the mass fraction of the tetraethoxysilane solution is 99%.

[0023] Preferably, in step (3), the stirring time is 50-70 minutes.

[0024] Preferably, in step (3), the reaction temperature is 38-42° C. and the reaction time is 2.5-3.5 h.

[0025] Preferably, in step (3), the solid is washed 2-3 times with anhydrous ethanol.

[0026] Preferably, in step (3), the drying operation is: placing the washed solid under vacuum and drying at 90-110° C. for 1 h.

[0027] Preferably, in step (4), the lubricant is zinc stearate.

[0028] Preferably, in step (4), the amount of lubricant added is 0.03-0.05% of the mass of the insulating iron powder.

[0029] Preferably, in step (4), the pressure of the pressing molding is 600-1100 MPa.

[0030] Preferably, in step (4), the protective gas is nitrogen.

[0031] Preferably, in step (4), a segmented annealing method is adopted, and the specific process parameters are:

[0032] Stage 1: heating to 250-270°C at a heating rate of 5-10°C / min and keeping at this temperature for 30 min;

[0033] Stage 2: Adjust the temperature to 400-450℃ and keep it for 30min;

[0034] Stage 3: Heat to 550-600°C at a heating rate of 5-10°C / min and keep at this temperature for 5-20 minutes.

[0035] Preferably, in step (4), the drying temperature is 70-80°C.

[0036] Preferably, in step (4), the cooled material is placed in an ethanol solution and ultrasonically cleaned for 10-30 minutes.

[0037] Further preferably, the mass fraction of the ethanol solution is 85%.

[0038] The second aspect of the present invention provides an iron-based soft magnetic composite material prepared by the above preparation method.

[0039] Beneficial effects of the present invention:

[0040] The present invention uses water-atomized iron powders of different particle sizes for particle size grading, so that the iron powders with small particle sizes are filled in the pores between the iron powders with large particle sizes, and the water-atomized iron powders are subjected to fine reduction treatment, and the iron powders after fine reduction are passivated with a phosphoric acid solution to obtain phosphated iron powders; aminopropyltriethoxysilane and tetraethoxysilane are then used for insulation treatment to obtain insulating iron powders. Lubricants are then added, pressed and annealed to obtain an iron-based soft magnetic composite material.

[0041] The present invention uses two silane coupling agents, aminopropyl triethoxysilane and tetraethoxysilane, to treat the iron phosphide powder, and reacts to form a film on the surface of the iron phosphide powder, thereby ensuring that the inorganic oxide is fully combined with the Fe powder to drive the nano inorganic oxide to be deposited on the surface of the iron-based soft magnetic powder. At the same time, the damage to the insulating coating layer on the surface of the soft magnetic composite material during the pressing and annealing stages can be effectively reduced, and the obtained soft magnetic composite material has good insulation performance and low magnetic loss. In addition, the present invention uses aminopropyl triethoxysilane and tetraethoxysilane to perform insulation treatment together, which has a synergistic effect in reducing the magnetic loss of the iron-based soft magnetic material.

[0042] Specifically, during the preparation process of the soft magnetic composite material of the present invention, phosphoric acid is first used to passivate the iron powder, and the phosphoric acid has good adhesion and high uniformity with the matrix pure iron powder. The internal phosphoric acid reacts closely with the powder matrix to form a complete and dense inorganic insulating layer. After being treated with aminopropyltriethoxysilane and tetraethoxysilane, an organic insulating layer is formed. After pressing and annealing, the external silicon dioxide has a high high temperature resistance and can prevent the inner layer from decomposing at high temperatures. In particular, compared with a single layer of phosphoric acid or silicon dioxide insulating layer, this multi-layer insulating coating shows a structural crack deflection advantage during pressing. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 : Scanning electron microscope image of the iron-based soft magnetic composite material obtained in Example 1;

[0044] Figure 2 : Scanning electron microscope image of the iron-based soft magnetic composite material obtained in Example 2;

[0045] Figure 3 : Scanning electron microscope image of the iron-based soft magnetic composite material obtained in Example 3. DETAILED DESCRIPTION

[0046] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0047] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0048] The experimental materials used in the embodiments of the present invention are all conventional experimental materials in the art and can be purchased through commercial channels.

[0049] The water-atomized pure iron powder of the present invention was purchased from Shandong Luyin New Material Technology Co., Ltd., and the particle size of the water-atomized iron powder was ≤180 μm.

[0050] Example 1: Preparation method of iron-based soft magnetic composite material

[0051] (1) 80 mesh and 100 water atomized pure iron powder are mixed in a mass ratio of 2:1 to obtain iron powder, and the iron powder is placed in a hydrogen atmosphere and reduced at 700° C. for 30 min to obtain refined reduced iron powder; the refined reduced iron powder has a purity of more than 99.5%, a particle size of 75 μm, and a bulk density of 3.2 g / cm 3 ;

[0052] (2) phosphoric acid and anhydrous ethanol are mixed at a solid-liquid ratio of 1 g:40 mL to obtain a phosphoric acid solution; refined reduced iron powder and the phosphoric acid solution are mixed at an addition amount of 4 g:1 mL, and stirred at 65° C. for 50 minutes to passivate the refined reduced iron powder to obtain phosphated iron powder;

[0053] (3) mixing aminopropyltriethoxysilane, anhydrous ethanol and water in a mass ratio of 1:20:10 to obtain an aminopropyltriethoxysilane solution;

[0054] The iron phosphide powder and aminopropyltriethoxysilane solution were mixed at a material-liquid ratio of 1 g:2.5 mL, and stirred for 60 minutes to obtain a mixture; the mixture and a 99% tetraethoxysilane solution were then mixed at a mass fraction of 75 g:1 mL, and reacted at 40°C for 3 hours;

[0055] After the reaction is completed, the solid is collected, washed with anhydrous ethanol for 3 times, and then the washed solid is placed under vacuum and dried at 100° C. for 1 h to obtain insulating iron powder;

[0056] (4) adding zinc stearate to the insulating iron powder, wherein the amount of zinc stearate added is 0.04% of the mass of the insulating iron powder, performing room temperature pressing molding under a pressure of 850 MPa, and then performing stepwise annealing under a nitrogen atmosphere, wherein the process parameters of the stepwise annealing are:

[0057] Stage 1: heating to 260°C at a heating rate of 8°C / min and keeping at this temperature for 30 min;

[0058] Stage 2: Adjust the temperature to 425°C and keep it for 30 minutes;

[0059] Stage 3: heating to 575°C at a heating rate of 8°C / min and keeping at this temperature for 12 min;

[0060] After annealing, the material was cooled to room temperature, and the cooled material was placed in an ethanol solution with a mass fraction of 85% for ultrasonic cleaning for 20 minutes, and then dried at 75° C. to obtain an iron-based soft magnetic composite material.

[0061] The iron-based soft magnetic composite material prepared by the present invention is characterized in structure. Figure 1 As shown. Figure 1 It can be seen that the iron-based soft magnetic composite material prepared in the present invention has a complete coating structure, which shows that the pressing and annealing processes do not damage the insulating coating layer.

[0062] Example 2: Preparation method of iron-based soft magnetic composite material

[0063] (1) 80 mesh and 100 water atomized pure iron powder are mixed in a mass ratio of 2:1 to obtain iron powder, and the iron powder is placed in a hydrogen atmosphere and reduced at 650° C. for 25-35 minutes to obtain refined reduced iron powder; the refined reduced iron powder has a purity of more than 99.5%, a particle size of 150 μm, and a loose density of 3.0 g / cm 3 ;

[0064] (2) phosphoric acid and anhydrous ethanol are mixed at a solid-liquid ratio of 1 g:35 mL to obtain a phosphoric acid solution; refined reduced iron powder and the phosphoric acid solution are mixed at an addition amount of 2.5 g:1 mL, and stirred at 50° C. for 40 minutes to passivate the refined reduced iron powder to obtain phosphated iron powder;

[0065] (3) mixing aminopropyltriethoxysilane, anhydrous ethanol and water in a mass ratio of 0.8:20:10 to obtain an aminopropyltriethoxysilane solution;

[0066] The iron phosphide powder and aminopropyltriethoxysilane solution were mixed at a material-liquid ratio of 0.8 g:2.5 mL, and stirred for 50 min to obtain a mixture; the mixture and a 99% tetraethoxysilane solution were then mixed at a mass fraction of 50 g:1 mL, and reacted at 38°C for 2.5 h;

[0067] After the reaction is completed, the solid is collected, washed twice with anhydrous ethanol, and then placed under vacuum and dried at 90°C for 1h to obtain insulating iron powder;

[0068] (4) adding zinc stearate to the insulating iron powder, wherein the amount of zinc stearate added is 0.03% of the mass of the insulating iron powder, performing room temperature pressing molding under a pressure of 600 MPa, and then placing it in a nitrogen atmosphere for stepwise annealing, wherein the process parameters of the stepwise annealing are:

[0069] Stage 1: heating to 250°C at a heating rate of 5°C / min and keeping at this temperature for 30 min;

[0070] Stage 2: adjust the temperature to 400°C and keep it for 30 minutes;

[0071] Stage 3: heating to 550°C at a heating rate of 5°C / min and keeping at this temperature for 5 min;

[0072] After annealing, the material was cooled to room temperature, and the cooled material was placed in an ethanol solution with a mass fraction of 85% for ultrasonic cleaning for 10 minutes, and then dried at 70° C. to obtain an iron-based soft magnetic composite material.

[0073] The electron microscope image of the iron-based soft magnetic composite material prepared in this embodiment is as follows: Figure 2 As shown. Figure 2 It can be seen that the iron-based soft magnetic composite material prepared in this embodiment has a guaranteed coating, which shows that the pressing and annealing processes do not damage the insulating coating layer.

[0074] Example 3: Preparation method of iron-based soft magnetic composite material

[0075] (1) Mixing 80 mesh and 100 water-atomized pure iron powder in a mass ratio of 2:1 to obtain iron powder, placing the iron powder in a hydrogen atmosphere, and reducing it at 750° C. for 35 min to obtain refined reduced iron powder; the refined reduced iron powder has a purity of more than 99.5%, a particle size of 75-200 μm, and a bulk density of 3.5 g / cm 3 ;

[0076] (2) phosphoric acid and anhydrous ethanol are mixed at a solid-liquid ratio of 1 g:45 mL to obtain a phosphoric acid solution; refined reduced iron powder and the phosphoric acid solution are mixed at an addition amount of 5 g:1 mL, and stirred at 80° C. for 60 minutes to passivate the refined reduced iron powder to obtain phosphated iron powder;

[0077] (3) mixing aminopropyltriethoxysilane, anhydrous ethanol and water in a mass ratio of 1.2:20:10 to obtain an aminopropyltriethoxysilane solution;

[0078] The iron phosphide powder and aminopropyltriethoxysilane solution were mixed at a material-liquid ratio of 1.2 g:2.5 mL, and stirred for 70 min to obtain a mixture; the mixture and tetraethoxysilane with a mass fraction of 99% were then mixed at a ratio of 100 g:1 mL, and reacted at 42°C for 3.5 h;

[0079] After the reaction is completed, the solid is collected, washed with anhydrous ethanol for 3 times, and then placed under vacuum and dried at 110° C. for 1 h to obtain insulating iron powder;

[0080] (4) Add zinc stearate to the insulating iron powder, wherein the amount of zinc stearate added is 0.05% of the mass of the insulating iron powder, perform room temperature pressing and molding under a pressure of 1100 MPa, and then perform stepwise annealing in a nitrogen atmosphere, wherein the process parameters of the stepwise annealing are:

[0081] Stage 1: heating to 270°C at a rate of 10°C / min and keeping at this temperature for 30 min;

[0082] Stage 2: adjust the temperature to 450°C and keep it for 30 minutes;

[0083] Stage 3: heating to 600°C at a heating rate of 10°C / min and keeping at this temperature for 20 min;

[0084] After annealing, the material was cooled to room temperature, and the cooled material was placed in an ethanol solution with a mass fraction of 85% for ultrasonic cleaning for 30 minutes, and then dried at 80° C. to obtain an iron-based soft magnetic composite material.

[0085] The electron microscope image of the iron-based soft magnetic composite material prepared in this embodiment is as follows: Figure 3 As shown. Figure 3 It can be seen that the iron-based soft magnetic composite material prepared in this embodiment has a guaranteed coating, which shows that the pressing and annealing processes do not damage the insulating coating layer.

[0086] Comparative Example 1: Preparation method of iron-based soft magnetic composite material

[0087] The difference between this comparative example and Example 1 is that the iron phosphide powder is not subjected to the insulation treatment corresponding to step (3). The specific steps are:

[0088] Zinc stearate is directly added to the iron phosphide powder, wherein the amount of zinc stearate added is 0.04% of the mass of the insulating iron powder, and after pressing and molding, annealing, cooling, washing and drying are performed to obtain an iron-based soft magnetic composite material, wherein the preparation method of the iron phosphide powder, pressing and molding and annealing process parameters are the same as those in Example 1.

[0089] Comparative Example 2: Preparation method of iron-based soft magnetic composite material

[0090] The difference between this comparative example and Example 1 is that in step (3), only aminopropyltriethoxysilane solution is used for insulation treatment.

[0091] Comparative Example 3: Preparation method of iron-based soft magnetic composite material

[0092] The difference between this comparative example and Example 1 is that in step (3), only tetraethoxysilane solution is used for insulation treatment.

[0093] Test example:

[0094] The performance test was conducted by winding the wire on the pressure ring, and the number of magnetic winding coils was 100*100. The magnetic loss of the iron-based soft magnetic composite materials obtained in Example 1 and Comparative Examples 1-3 was detected using a soft magnetic material dynamic measurement device, and the results are shown in Table 1. At the same time, the saturation magnetization intensity of the iron-based soft magnetic composite materials obtained in Example 1 and Comparative Examples 1-3 was detected, and the results are shown in Table 1.

[0095] Table 1 Magnetic loss and resistance saturation magnetic loss

[0096]

[0097] It can be seen from Table 1 that under the conditions of 50Hz and 1T, the magnetic loss of the iron phosphide powder in Comparative Example 1 is 9.40W / kg, while in Comparative Example 2, aminopropyltriethoxysilane is modified on the iron phosphide powder as an organic insulating layer, and its magnetic loss is 6.65W / kg, which is 2.75W / kg lower than that in Comparative Example 1; in Comparative Example 3, tetraethoxysilane is modified on the iron phosphide powder as an organic insulating layer, and its magnetic loss is 6.2W / kg, which is 3.17W / kg lower than that in Comparative Example 1. The soft magnetic composite material prepared in this application is modified with aminopropyltriethoxysilane and tetraethoxysilane on the iron phosphide powder, and its magnetic loss is 2.76W / kg. It can be seen that the present invention uses aminopropyltriethoxysilane and tetraethoxysilane as organic insulating layers, which have a synergistic effect in reducing the magnetic loss of the soft magnetic composite material. In addition, the saturation magnetization of the iron-based soft magnetic composite material prepared by the present invention can reach 1.37.

[0098] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing an iron-based soft magnetic composite material, characterized in that: The following steps are involved: (1) performing fine reduction treatment on the iron powder to obtain fine reduced iron powder; (2) adding phosphoric acid solution to the refined reduced iron powder and stirring to passivate the refined reduced iron powder to obtain phosphated iron powder; (3) adding iron phosphide powder to aminopropyltriethoxysilane solution and stirring to obtain a mixture; adding tetraethoxysilane to the mixture for reaction, and after the reaction is completed, washing and drying to obtain insulating iron powder; (4) After adding lubricant to the insulating iron powder, pressing and molding, annealing in a protective gas atmosphere, cooling, washing and drying, the iron-based soft magnetic composite material is obtained.

2. The method for preparing the iron-based soft magnetic composite material according to claim 1, characterized in that: The operation of fine reduction treatment of iron powder is as follows: placing the iron powder in a hydrogen atmosphere and treating it at 650-750° C. for 25-35 minutes to obtain fine reduced iron powder.

3. The method for preparing the iron-based soft magnetic composite material according to claim 1, characterized in that: In step (2), the phosphoric acid solution is prepared by mixing phosphoric acid and anhydrous ethanol in a solid-liquid ratio of 1 g: (35-45) mL; the solid-liquid ratio of refined reduced iron powder to phosphoric acid solution is (2.5-5) g: 1 mL; the stirring temperature is 50-80° C., and the stirring time is 40-60 min.

4. The method for preparing the iron-based soft magnetic composite material according to claim 1, characterized in that: In step (3), the aminopropyltriethoxysilane solution is prepared by mixing aminopropyltriethoxysilane, anhydrous ethanol and water in a mass ratio of (0.8-1.2):20:10; the material-liquid ratio of the iron phosphide powder and the aminopropyltriethoxysilane solution is (0.8-1.2) g:2.5 mL.

5. The method for preparing the iron-based soft magnetic composite material according to claim 1, characterized in that: In step (3), the material-liquid ratio of tetraethoxysilane solution to the mixture is 1 mL: (50-100) g.

6. The method for preparing the iron-based soft magnetic composite material according to claim 1, characterized in that: In step (3), the stirring time is 50-70 minutes; the reaction temperature is 38-42° C., and the reaction time is 2.5-3.5 hours.

7. The method for preparing the iron-based soft magnetic composite material according to claim 1, characterized in that: In step (4), the lubricant is zinc stearate, and the amount of the lubricant added is 0.03-0.05% of the mass of the insulating iron powder.

8. The method for preparing the iron-based soft magnetic composite material according to claim 1, characterized in that: In step (4), the pressure of compression molding is 600-1100 MPa.

9. The method for preparing the iron-based soft magnetic composite material according to claim 1, characterized in that: In step (4), segmented annealing is adopted, and the specific process parameters are: Stage 1: heating to 250-270°C at a heating rate of 5-10°C / min and keeping at this temperature for 30 min; Stage 2: Adjust the temperature to 400-450℃ and keep it for 30min; Stage 3: Heat to 550-600°C at a heating rate of 5-10°C / min and keep at this temperature for 5-20 min.

10. The iron-based soft magnetic composite material prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Soft magnetic composite material with high saturation magnetic flux density and low loss and preparation method thereof

    CN110246675A

Cited By

  • Alloy soft magnetic powder for differential mode inductor and preparation process and application of alloy soft magnetic powder

    CN120998619A

  • Preparation method of copper-plated soft magnetic composite material, soft magnetic composite material and application of soft magnetic composite material

    CN122177615A